School health - Muhad Maran, Muhamad Mazlan; Rosnani, Sarkarsi; Wan Harun, Wan Nur Shuhada; Azizan, Nurul Idawawiyah; Syed Elias, Sharifah Munirah (IIUM Press, 2018)
This research e-book is a compilation of few researches conducted in secondary school in Kuantan, Pahang. These researches were related to current issues in school, for instance, childhood obesity and bully which involved students and teachers as the participants. Chapter 1 – presented a study on sex education in secondary school in Kuantan, Pahang, Malaysia. This cross-sectional study was to determine the awareness and the knowledge of school teachers regarding sexual education. This study was conducted among 149 secondary school teachers who enrolled in the selected three schools at Kuantan. The instrument used was the National Survey of Secondary Teachers of Sexuality Education Questionnaire to measure the level of knowledge and awareness among the respondents. The data was analysed using SPSS xiv Preface version 19 in term of descriptive analysis, and Correlation, Independent T-test and ANOVA test were carried out for significant test. Overall, this study found that the majority of secondary school teachers were knowledgeable about sexual education. Yet, there were small proportion of the them were less aware about the sexual education. Chapter 2 –presented a study on smoking behaviour among secondary school student. The aim of the study was to identify the factors influencing smoking practice among adolescents. It was a quantitative descriptive cross-sectional study design. The data were collected from 323 students from three secondary schools in Kuantan Pahang by using questionnaire based on inclusion and exclusion criteria. The data were analyzed by using SPSS version 19 in term of descriptive analysis and Chi Square test were carried out for significant test. This study showed that there were small proportion of the respondents can be considered as ever smokers. Factors such as age, gender, nearest people who smoke around, and attitudes of the student have significant association with the smoking status.Chapter 3 – presented a study related to bully in school. This cross-sectional study was to explore the association between bully and depression among secondary school student. 377 students were selected using convenience sampling from the three selected shools in Kuantan, Pahang.The instruments are Multidimensional Peer-Victimization Scale, Cyber Bullying and Online Aggression Survey and Patient Health Questionnaire (PHQ-9). The data had been analyze using SPSS version 20 in term of descriptive analysis and Chi-Square Test were carried out for significant result. The findings of the study showed that 22% of respondents are having moderate depression and the rest are having only mild level of depression. For the association between socio- demographic factor and level of depression, there are a significant association between level of study gender and parents‟ education level. Types of bully also show a significant association with level of depression. The majority of secondary school students at Kuantan are only having mild and moderate level of depression but there are a significant number of xvi Preface bully were identified. Thus, the relevant authorities such as school administration with the assistance of the public should take an essential precaution in order to prevent this condition from getting worse.